Influence of Self-Efficacy and Resilience on Subjective Well-Being: A Study of the New Curriculum Implementation in Indonesia - Adam Rusydi; Waspodo Tjipto Subroto; Norida Canda Sakti (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This research was purposely conducted to determine how teachers’ self-efficacy and resilience influence their subjective well-being, especially in implementing new curriculum policies. Method: This research was a correlational study, while the data were collected from 50 respondents and selected using an incidental sampling technique. The questionnaire was employed to gather the data, and SEM analysis using the SmartPLS program was used to analyze data. Results: Both self-efficacy and resilience had influences on teachers’ subjective well-being. Furthermore, resilience was categorized as high in two of the eight resilience indicators. Meanwhile, one of the five subjective well-being indicators was removed due to the examination of indicator or factor loading values in this study. Novelty: This research differed from others as it primarily addressed the variables used in this research individually and still needed to correlate them as factors that possibly influence each other. Moreover, it provides a new perspective on curriculum development by considering teachers' subjective well-being from a non-financial point of view.